Effect of different sources of farm yard manure, Jeevamrutha and panchgavya on growth and yield of French bean (Phaseolus vulgaris L) var. Paulista - Arvind Kumar (Annals of Agricultural Research, 2025)
A field experiment was conducted at Agricultural Research Farm, AISECT University, Hazaribag, Jharkhand during 2024 to study the combined effect of FYM and liquid manures (Jeevamruth and Panchagvya) on growth and yield of French bean. The experiment was laid out in Randomized Block Design (RBD) with twelve treatments and control which were replicated thrice. Application of FYM in term of 100%, 150% and 200% N and soil application of Jeevamrutha (3%, 5% and 7% or 1000lt/ hect.) and foliar spray of Panchgavya (3%, 5% and 7%) recorded viz. no of seed emergence per plot (%), No of primary branches, plant height (cm), pod length (cm), number of pods per plant, pod weight per plant (gm) and green pod yield (q/hect). The experiment of liquid organic matter such as FYM, Jeevamrutha and Panchgavya leads to an increase in the number of beneficial micro-organism activity of the soil and increased of yield were significantly higher compared to the other treatments.